1965
DOI: 10.1021/bi00880a019
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Acid Sequence Around the “Reactive” Sulfhydryl Groups in Adenosine Triphosphocreatine Phosphotransferase*

Abstract: A number of sulfhydryl reagents react in tained in over 50% yield. This indicates that stoichiometric proportions to inactivate adenosine both reactive sulfhydryl groups have the same triphosphocreatine (ATP-creatine) phosphotransferase.amino acid sequence throughout these eight Two sulfhydryl groups of the six available on the amino acids. The sequence about these two reacenzyme are preferentially attacked by these reagents.tive sulfhydryl groups is Val-Leu-Thr-CySH-Pro-Ser-Two equivalents of 2,4-dinitrofluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1967
1967
1999
1999

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Attempts have been made to achieve group specificity in dinitrophenylation by using less reactive reagents (e.g, dinitrobenzenesulfonic acid [5]) or by performing the reaction at a pH at which some of the functional groups are relatively much less reactive [6]. However, in practice it was found that the reactivity of certain functional groups in a protein is so much influenced by their microenvironment that it is often possible to find reaction conditions under which FDNB can be led quite selectively not only to one type of functional group but rather to a unique group within a specific site of the protein [7][8][9][10][11].A few years ago we showed [12] that DNP derivatives of sulfhydryls, imidazole irnino-nitrogens, and phenolic hydroxyIs (but not of Q and e amino groups) can be easily displaced by thiols, thus converting dinitrophenylation into a reversible tech- …”
mentioning
confidence: 99%
“…Attempts have been made to achieve group specificity in dinitrophenylation by using less reactive reagents (e.g, dinitrobenzenesulfonic acid [5]) or by performing the reaction at a pH at which some of the functional groups are relatively much less reactive [6]. However, in practice it was found that the reactivity of certain functional groups in a protein is so much influenced by their microenvironment that it is often possible to find reaction conditions under which FDNB can be led quite selectively not only to one type of functional group but rather to a unique group within a specific site of the protein [7][8][9][10][11].A few years ago we showed [12] that DNP derivatives of sulfhydryls, imidazole irnino-nitrogens, and phenolic hydroxyIs (but not of Q and e amino groups) can be easily displaced by thiols, thus converting dinitrophenylation into a reversible tech- …”
mentioning
confidence: 99%
“…Amino acid sequences around the reactive cysteine residues of creatine kinase, arginine kinase and lmbricine kinase. The sequence for creatine kinase from rabbit muscle was determined by Thomson et al [3] and Mahowald [28], and that from OX brain by Atherton et al [ 5 ] ; the sequence for arginine kinase was determined by Der Terrossian et al [6] of creatine kinase tryptic peptide whereas its C-terminal sequence can be superimposed on the same portion of arginine kinase tryptic peptide. The deletion of one amino acid (glycine or threonine) next to the proline in creatine kinase peptides is compensated by the addition of one glycine in the C-terminal region.…”
Section: Discussionmentioning
confidence: 99%
“…At pH 8, the molar absorption value of S-Niph-cysteine in the protein was assumed t o be I I .3 mM-l cm-l at 340 nm according to Mahowald [13]. An aliquot of 1Omg dialyzed enzyme was diluted in I mM EDTA, 0.04M NaHCO, buffer pH 8 to a final volume of I ml (enzyme concentration 125 $ I ) and allowed to equilibrate at 4 "C in a 1-cm quartz cell.…”
Section: Reaction Of Lombricine Kinase With 24-dinitrofluorobenzenementioning
confidence: 99%
“…This reagent was previously used to label the two essential -SH groups of creatine kinase [13,27]. The inhibition studies and the stoichiometry of the reaction of N,ph-F with lombricine kinase provided evidence that this reagent is indeed specific to the essential -SH group of this enzyme.…”
Section: Separation Of the Essential -Sh-containing Tryptic Peptide Fmentioning
confidence: 99%